PROBLEMATIKA IMPLEMENTASI PROGRAM BERAS MISKIN (RASKIN) DI KOTA PEKANBARU TAHUN 2012 - ", Isril; Shalehah, Sri Mar’atus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Rice which addresses for poor families (Raskin) is the part of poverty prevention in 1st cluster, that is a family based social protection in fulfillment of basic food needs for disadvantaged communities. Raskin has multifunction that is strengthen the poor family food resistance as the support for increasing quality of human resource, as the support of farming and another sector and increasing the economic empowerment in region. Besides, Raskin has direct impact in stabilization the rice of price which finally also has role in keeping the stability of national economic.The research aims to discover the problematic that happens in the implementation of Raskin Program in Pekanbaru on 2012 and to discover the factor that causes its problematic emerges in consideration of the implementation of Raskin Progam in Pekanbaru on 2012.The research uses the combination among qualitative and quantitative with descriptive approach. The primer data achieved from the interview result with the respondents who know about Raskin; the secondary achieved from the agency which bounded, such as Office of Economic Administration, district office of Tenayan Raya, and Office Groove of Sail.The result of the research shows that; the problematic of Raskin Program implementation in Pekanbaru on 2012 runs less effective. The indicators that made it ran less effective are; right on target, quality, price, administration. Factors that prompt; non-valid RTS data establishment, the groove staffs are not routinely to request the Raskin monthly, the distance between house RTS-PM Raskin with the distribution spot is far, lack of supervision about the rice quality by groove, duration of depositing money as the redeem prices for raskin (HTR) from RW to village, and lack of socialize about Raskin Program to RTS-PM Raskin.Keyword: Problematic, Beras Miskin (Raskin), Policy.